Ecology and morphology of mouse lemurs (Microcebus spp.) in a hotspot of microendemism in northeastern Madagascar, with the description of a new species. Issue 9 (27th July 2020) - Schüßler, Dominik; Blanco, Marina B.; Salmona, Jordi; Poelstra, Jelmer; Andriambeloson, Jean B.; Miller, Alex; Randrianambinina, Blanchard; Rasolofoson, David W.; Mantilla‐Contreras, Jasmin; Chikhi, Lounès; Louis, Edward E.; Yoder, Anne D.; et al.
Abstract: Delimitation of cryptic species is increasingly based on genetic analyses but the integration of distributional, morphological, behavioral, and ecological data offers unique complementary insights into species diversification. We surveyed communities of nocturnal mouse lemurs ( Microcebus spp.) in five different sites of northeastern Madagascar, measuring a variety of morphological parameters and assessing reproductive states for 123 individuals belonging to five different lineages. We documented two different non‐sister lineages occurring in sympatry in two areas. In both cases, sympatric species pairs consisted of a locally restricted ( M. macarthurii or M . sp. #3) and a more widespread lineage ( M. mittermeieri or M. lehilahytsara ). Estimated Extents of Occurrence (EOO) of these lineages differed remarkably with 560 and 1, 500 km 2 versus 9, 250 and 50, 700 km 2, respectively. Morphometric analyses distinguished unambiguously between sympatric species and detected more subtle but significant differences among sister lineages. Tail length and body size were most informative in this regard. Reproductive schedules were highly variable among lineages, most likely impacted by phylogenetic relatedness and environmental variables. While sympatric species pairs differed in their reproductive timing ( M . sp. #3/ M. lehilahytsara and M. macarthurii/M. mittermeieri ), warmer lowland rainforests were associated with a less seasonal reproductive schedule for M. mittermeieri and M. lehilahytsara compared with populations occurring in montane forests. Distributional, morphological, and ecological data gathered in this study support the results of genomic species delimitation analyses conducted in a companion study, which identified one lineage, M . sp. #3, as meriting formal description as a new species. Consequently, a formal species description is included. Worryingly, our data also show that geographically restricted populations of M . sp. #3 and its sister species ( M. macarthurii ) are at high risk of local and perhaps permanent extinction from both deforestation and habitat fragmentation. Abstract : The newly described Jonah's mouse lemur ( Microcebus jonahi ) is distributed in northeastern Madagascar with an estimated Extent of Occurrence of about 1, 500 km 2 . This species has a mean head‐body length of 13.0 cm, a mean tail length of 13.3 cm and weighs on average 57.4 g. Highlights: Two pairs of Microcebus species occur in partial sympatry. Morphological distinctiveness supports genomic species delimitation in cryptic lemurs. High plasticity in reproductive schedules in a lineage of habitat generalists detected.